Changes in polyamine content are related to low temperature resistance in potato plants (1999)
Polyamine content and variation within a 48 hour simulated freezing stress were determined in plants with different low temperature resistance. Genotypes Solanum acaule, Solanum phureja, transgenic Solanum tuberosum c.v. Desiree with antifreezing trans-genes from Winter Flounder and the clone 88-35-7 (tbr- (atzimba) x (acl x phu ccc8l) were used for the experiment. Tolerant species 5. acaule was the only one that survived freezing stress (80% surviving tissue) the others had more than 50% of dead tissue by the end of the experiment. Clone 88-35-7 died slower than S. phureja and transgenic plants of Desiree. This response was related to free putrescine and free spermidine titters of 5. acaule plants and in less extend in clone 88-35-7 plants. Polyamine concentration was low and stable in sensitive plants (5. phureja and Desiree) within freezing condition. Soluble bound forms ofpolyamines were the source for Put and Spm increase in 5. acaule and 88-35-7 plants. As a result, soluble bound polyamine titer decreased with the freezing stress.